The Role of Epistemological Belief and Self Regulation in Academic Procrastination of Muslim College Students - M. Nur Ghufron; Rini Risnawita Suminta (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung in collaboration with Asosiasi Bimbingan dan Konseling Indonesia (ABKIN), 2022)
The study on academic procrastination can help educators and educational developers in avoiding the lack of success and even failure in the educational process. This study aims to examine the effect of belief about knowledge, belief about learning, and self-regulation in learning on academic procrastination. This quantitative study involves 277 college students. The data collection technique used in this study is a questionnaire in the form of a scale. There are four types of scales used in the data collection process: the scale of belief about knowledge, the scale of belief about learning, the scale of self-regulation in learning, and the scale of academic procrastination. Data analysis technique using structural equation technique. The results show that belief about knowledge has an effect on self-regulation in learning (r = 0.157, p = 0.028), belief about knowledge affects academic procrastination (r = -0,157, p = 0.000), belief about learning affects self-regulation in learning (r = 0.199, p = 0,040), belief about learning affects academic procrastination (r = -0.147, p = 0,019), and self-regulation in learning affects significant negatively to academic procrastination (r = -0.097, p = 0,030).